2000
DOI: 10.1007/s002400000121
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell death and fertility in three unilateral cryptorchid rat models

Abstract: Three rat strains have been studied, using a sensitive apoptotic detection method for germ-cell degeneration, to resolve the controversy regarding the effect of cryptorchidism on the contralateral descended testis (CDT). Sprague Dawley and Buffalo rats were made cryptorchid by operation at 20-22 days of age, while trans-scrotal (T-S) rats were a congenitally unilateral cryptorchid strain. Sham operated rats or normal T-S littermates were used as controls. Experiments were performed over a period ranging from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…Our results show that temperature is indeed one factor that can trigger apoptosis in the cauda epididymidis. Temperature-induced apoptosis has already been described in the testes in cases of cryptorchidism, both spontaneous and experimental [37][38][39][40]. It is noteworthy that, in our case, this temperatureinduced apoptosis was region dependent, being restricted to the proximal tubules of the cauda.…”
Section: Discussionmentioning
confidence: 36%
“…Our results show that temperature is indeed one factor that can trigger apoptosis in the cauda epididymidis. Temperature-induced apoptosis has already been described in the testes in cases of cryptorchidism, both spontaneous and experimental [37][38][39][40]. It is noteworthy that, in our case, this temperatureinduced apoptosis was region dependent, being restricted to the proximal tubules of the cauda.…”
Section: Discussionmentioning
confidence: 36%
“…Germ cells in both types of gonads are very sensitive to pathological stimuli. It has been reported that testicular germ cell degeneration occurs during various stages of spermatogenesis under experimentally manipulated conditions, such as cryptorchidism (Shikone et al, 1994;Yin et al, 1998;Watts et al, 2000;Xu et al, 2000), ischemia-reperfusion (Turner et al, 1997;Shiraishi et al, 2000;Koji et al, 2001), hypophysectomy (Russell and Clermont, 1977), treatment with GnRH antagonists (Billig et al, 1995;Hikim et al, 1995), heating (Yamamoto et al, 2000;Miura et al, 2002), and drug treatment (Nonclercq et al, 1996;Lee et al, 1997;Nandi et al, 1999;Franca et al, 2000;Zhu et al, 2000;Yu et al, 2001). In addition, Nandi et al reported that reduction of intratesticular testosterone due to Leydig cells degeneration by treatment with ethane 1,2-dimethanesulfonate (EDS) indirectly induces germ cell apoptosis (Nandi et al, 1999).…”
Section: Pathological Cell Death In the Reproductive Organsmentioning
confidence: 99%
“…4 No spermatids, few spermatocytes, arrest of spermatogenesis at the primary spermatocyte stage. 3 Spermatogonia only. Mothers of the control rats were injected in utero with only the vehicle, and those of the model rats were treated with 2.5-15 mg flutamide per day per body on gestation days 14-20.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zimmermann et al 10 described the Insl3 knockout mouse as cryptorchid animal model, and Overbeek et al 11 also reported the transgenic mouse model. To our knowledge, most of the experimental animal models for cryptorchidism have been made by surgical methods, [3][4][5][6][7] that is, displacement of the normal descended testes. By such methods, however, the influence of the surgical stress on testicular tissue could not be completely denied.…”
Section: Discussionmentioning
confidence: 99%